Community Development dalam Penerapan Nilai-Nilai Moral Kristiani di SMAK Setia Bakti Ruteng, Kabupaten Manggarai - Keristian Dahurandi; Paulus Tolo; Fredrikus Djelahu Maigahoaku (Jurnal Penelitian Pendidikan Agama Katolik, 2022)
Character building is an accentuation of Indonesian educational project today. The mandate of the Preamble of the 1945 Constitution in the fourth paragraph indicates the goal of education that is to educate the nation's life. The mandate is operationally implemented in the strategic plan of formal education through the “2013 Curriculum” design which emphasizes "improvement of noble character". There are various noble character values that want to be instilled in students. One of the important character values is religious moral value. The main concern of Setia Bhakti Ruteng Senior High School in Manggarai Regency of Nusa Tenggara Timur Province is promoting moral-religious value among its students. In accordance with the spirit of the SSpS Sisters (Servorum Spiritu Sancto) – the owner of the school – Catholic values are the focus educational process. The Catholic values such as cooperation, honesty, responsibility, faith/trust, sacrifice, humility, and love must span the student’s behaviours. The results of the pre-test done showed that three values: cooperation, honesty, and responsibility, are considerable unsatisfactory among the students. Based on the result, an action should be taken by applying an action research method. The method used in this research – based on the method of Kemis and McStagart – consists of pre-action stage, first cycle action and second cycle action. Internalization process of Catholic moral values at each stage uses community development approach. The results of the action show that the community development approach has a positive trend with a score of 62%. This means the community development approach taken can increase 62% of Christian moral values of students at SMAK Setia Bhakti Ruteng.